Universal One-Parametric Dependence of Dielectric Water and Water Steam Permeability on Density-Temperature Ratio - Yu. V. Mulev; K. M. Arefiev; O. V. Beliayeva; M. Yu. Mulev; T. A. Zaiats (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
Available experimental data on dielectric permeability of water and water steam have been analyzed in the paper. The paper presents an universal one-parametric dependence of dielectric water and water steam permeability in single-phase areas and also on boundary curves on density -temperature ratio.